Patterned enteroscopy balloon design factors influence tissue anchoring - Bowen, Leah K.; Johannes, Karl; Zuetell, Emily; Calahan, Kristin N.; Edmundowicz, Steven A.; Long, Rong; Rentschler, Mark E. (Journal of the mechanical behavior of biomedical materials, 2020)
Balloon-assisted enteroscopy procedures allow visualization and intervention in the small intestine. These balloons anchor an endoscope and/or overtube to the small intestine, allowing endoscopists to plicate the small intestine over the overtube. This procedure can extend examination deeper into the small intestine than the length of the endoscope would allow with direct examination. However, procedures are often prolonged or incomplete due to balloon slippage. Enteroscopy balloons are pressure-limited to ensure patient safety and thus, improving anchoring without increasing pressure is essential. Patterning balloon exteriors with discrete features may enhance anchoring at the tissue-balloon interface. Here, the pattern design space is explored to determine factors that influence tissue anchoring. The anchoring ability of smooth versus balloons with patterned features is investigated by experimentally measuring a peak force required to induce slippage of an inflated balloon inside ex-vivo porcine small intestine. Stiffer materials, low aspect-ratio features, and pattern area/location on the balloons significantly increase peak force compared to smooth silicone balloons. Smooth latex balloons, used for standard enteroscopy, have the lowest peak force. This work demonstrates both a method to pattern curved surfaces and that a balloon with patterned features improves anchoring against a deformable, lubricated tissue interface. [Display omitted]